(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
The research concluded by explaining the role of government investment in achieving growth and development, which attracts the attention of all countries because investing in the available capabilities in an optimal way, such as the human, natural and financial resources of any country, is the basic foundation for building a sound and strong economy capable of facing challenges and solving many problems that countries suffer from, such as poverty and unemployment, and achieving growth requirements. and development. For this purpose, countries are always searching for how to improve their investment climate and use their resources optimally, and identify a set of political, economic, social and financial factors that affect the volume and directions of government investment. In order to achieve the main goal of the study, which is to demonstrate the extent of the impact of government investment on a number of macroeconomic variables, including gross domestic product, the path analysis method was used for the purpose of determining the size and impact of government investment in each of (domestic product, inflation, and private investment), and the study concluded that Government investment has a moral and positive impact on economic growth, in addition to having direct and indirect effects on the workforce and capital formation.